2016
DOI: 10.4103/1947-2714.187131
|View full text |Cite
|
Sign up to set email alerts
|

The usage of social networking sites by medical students for educational purposes: A meta-analysis and systematic review

Abstract: Background:Online social networking sites (SNSs) (e.g., Facebook, MySpace, Flickr, Twitter and YouTube) have emerged as rapidly growing mechanisms to exchange personal and professional information among university students. This research aims to determine the medical students’ extent of usage of SNSs for educational purposes.Materials and Methods:Educational Resources Information Centre (ERIC), Cumulative Index of Nursing and Allied Health Literature (CINAHL), the Cochrane library, and Excerpta Medica Data Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 40 publications
2
89
3
5
Order By: Relevance
“…In terms of the educational use of SNSs, students use these platforms for putting together presentations, timetabling and using calendar of activities, developing collaborative group work, group discussions, facilitating and evaluating learning, faculty support, and for updating regional and global knowledge. A systematic review and meta-analysis by Guraya [7] has reported that 20% of the university medical students used SNSs in sharing information for educational purposes. However, the study could not find any study that envisaged to determine the impact of SNSs on the students’ academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the educational use of SNSs, students use these platforms for putting together presentations, timetabling and using calendar of activities, developing collaborative group work, group discussions, facilitating and evaluating learning, faculty support, and for updating regional and global knowledge. A systematic review and meta-analysis by Guraya [7] has reported that 20% of the university medical students used SNSs in sharing information for educational purposes. However, the study could not find any study that envisaged to determine the impact of SNSs on the students’ academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, there are more than one billion active users of Facebook (Facebook, 2017) and YouTube (YouTube, 2017), and over 300 million active monthly users of Twitter (Twitter, 2017). These figures include high levels of SoMe activity among undergraduate students for educational as well as social purposes (Ali, 2016;Guraya, 2016;Knight-McCord et al, 2016;Roblyer, McDaniel, Webb, Herman, & Witty, 2010;Tess, 2013) and such usage parallels the availability of remote SoMe access achieved through uptake in smart devices (Buchholz, Perry, Weiss, & Cooley, 2016;Evrim, 2014;Gökçearslan, Mumcu, Haşlaman, & Çevik, 2016;Ozdalga, Ozdalga, & Ahuja, 2012;Ponce, Méndez, & Peñalvo, 2014). In the early to mid2000s, SoMe and Web 2.0 arose as new, exciting and innovative technologies (Boyd & Ellison, 2007) that instructors began to incorporate into educational activities (Booth & Hultén, 2003;Mazer, Murphy, & Simonds, 2007) and the increasing interest in SoMe during this period is reflected in the volume of educational literature on this topic (Asiri & Househ, 2016;Aydin, 2012;Kakushi & Evora, 2016;Lafferty & Manca, 2015;McAndrew & Johnston, 2012;Pander, Pinilla, Dimitriadis, & Fischer, 2014;& Cochran, 2012), blurring of the staff-student boundary (Mazer et al, 2007); unprofessional usage (Kitsis et al, 2016); and impacts on lecturer credibility (Hutchens & Hayes, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, social networking sites and applications have introduced new opportunities for learners and medical educators to share, edit, and comment on information through video-sharing sites, such as YouTube [12,13]. YouTube, the largest Internet video-sharing site, has been used extensively for patient, public, and health professional education [14,15].…”
Section: Introductionmentioning
confidence: 99%